Risk Factors Associated With Recurrent Hamstring Injuries in Sports Athletes: Risk Factors of Recurrent Hamstring Injuries - Shahid, Qurat ul Ain; Bukhari, Bazal; Ghaffar, Hassan Abdul; Hashim, Adnan; Sheeraz, Muhammad; Ali, Sarwat (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2020)
Hamstring injuries are commonly strained and occur proximally around the muscle-tendon junction, injuring the biceps femoris laterally. Gashes, wounds, and strains are three different types of muscle damage depending on the event instrument. Objective is to assess recurrent hamstring injuries in sports athletes Methods: A cross-sectional research was observed in 183 participants .18 to 35 years were observed. Special informed consents were gathered from the participants before the study. Most of the participants were student athletes of the University of Lahore. Data was collected using a non-probability handy sampling strategy. SPSS statistics v. 25 was used to analyze the data. Results: Participants in the sample were on average 24.69 years old, the youngest is eighteen years old, while the oldest is thirty-four years old. In this study included both genders .102 were males (55.7%) and 81 female (44.3) participants, with 27 of the participants married and 4 divorced individuals. 35.% of the athletes play Football, 11.5% play Basketball, 14.8% play both Football and Basketball. While, 23.5% play Cricket and only 14.8% play Badminton. 36.6% of the participants had playing experience of 5 years or more. While others averaged between 1-4 years of experience. Only 75 of the 183 participants indicated that they stretched 5 minutes before any exercise or sports. 63 participants stretched 10 minutes before any exercise or sports. While, only 13 claimed they stretched for 20 minutes and 2 participants stretched for 25 minutes. A history of previous injury was noted in 48.6% of athletes, while 51.4% claimed to not have had any previous injury. Positive pain or tightness in the thighs was noted for 134 (73.2%) athletes. 48.6% of the dataset population had a recurrent hamstring injury. While, 51.4% did not. Conclusions: Notable associations were noted for hamstring injuries with stretching of muscles, muscle tightness, low back pains, inadequate warm-ups before playing and playing days after the occurrence of an injury. Results also shows that fatigue and old age is not a strong risk factor for the recurrence of hamstring strain.